Reconciling Customary Law and Cultural Practices with Human Rights in Uganda - Mujuzi, Jamil Ddamulira (Obiter, 2020)
Customary law has been part of Ugandan law for many years. Section 2 of the Local Council Courts Act, 2006 defines “customary law” to mean “the rules of conduct established by custom and long usage having the force of law and not forming part of the common law nor formally enacted in any legislation”. Ugandan courts have explained the relationship between customary law and other laws. In 1995, Uganda adopted a constitution that includes, among other things, a bill of rights that prohibits discriminatory and degrading laws and customs. This was informed during the making of the Constitution by the arguments of many Ugandans that discriminatory and degrading customary practices and laws should be abolished by the Constitution. In this article, the author illustrates the steps that have been taken by the drafters of the Constitution, Parliament (through legislation) and courts to outlaw discriminatory and degrading cultural practices. The author recommends ways in which some of these measures could be strengthened.